1996
DOI: 10.1128/jvi.70.5.3227-3234.1996
|View full text |Cite
|
Sign up to set email alerts
|

Second-strand synthesis is a rate-limiting step for efficient transduction by recombinant adeno-associated virus vectors

Abstract: The ability of recombinant adeno-associated virus (AAV) to transduce cells with a marker gene in vitro was found to be substantially increased by the presence of adenovirus. Transfection experiments with adenovirus genomic DNA suggest that this increase is not facilitated by adenovirus-mediated viral uptake but is instead dependent on adenovirus gene expression. Using various adenovirus mutants, we were able to map this function to early-region E4 open reading frame 6. Plasmid expression of open reading frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
234
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 677 publications
(252 citation statements)
references
References 45 publications
13
234
0
1
Order By: Relevance
“…In contrast, the primary target of the genotoxic agent HU is thought to be ribonucleotide reductase. It is unclear precisely how transduction of rAAV is enhanced following these treatments, but MG132 and HU are postulated to increase efficiency of nuclear entry (20,22,69). Here we demonstrate that the aforementioned pharmacological agents can regulate accumulation and mobilization of intact AAV virions in the nucleus following infection using a variety of techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the primary target of the genotoxic agent HU is thought to be ribonucleotide reductase. It is unclear precisely how transduction of rAAV is enhanced following these treatments, but MG132 and HU are postulated to increase efficiency of nuclear entry (20,22,69). Here we demonstrate that the aforementioned pharmacological agents can regulate accumulation and mobilization of intact AAV virions in the nucleus following infection using a variety of techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is unclear whether capsids enter the nucleus intact, it has been well established that nuclear delivery of the genome is highly inefficient and significantly limits transduction. Several studies have identified agents that surmount subcellular barriers to transduction (20,22,69). Two of the most well-documented agents known to improve subcellular processing are proteasome inhibitors and hydroxyurea (HU); however, their mechanisms of action remain unknown.…”
mentioning
confidence: 99%
“…1,2 Recombinant AAV (rAAV) is also a useful tool for liver-directed gene delivery because the virus can infect nondividing cells, integrate specifically into the host cell genome, and is relatively nonpathogenic compared with more commonly used adenoviral vectors. 1 Although rAAV provides many advantages over other vectors, its transduction efficiency in many tissues, including the liver, is limited either because of the requirement of synthesis of the second strand of DNA in the viral genome 3,4 or because of the lack of transgene expression caused by decreased promoter activity (i.e., inactivation of the cytomegalovirus [CMV] promoter). 5 Second-strand synthesis of the single-stranded AAV viral genome, which is required for the expression of the transgene, is hypothesized to be the limiting step in transduction; however, the cellular mechanisms for this process remain unclear.…”
mentioning
confidence: 99%
“…Various genotoxic agents, such as etoposide and hydroxyurea, as well as coinfection with helper viruses such as adenovirus or herpes virus, have been shown to increase rAAV transduction. 3,4,6 Moreover, many agents shown to increase rAAV transduction in vitro also cause mild cellular damage and induce many cellular stress responses such as activation of nuclear transcription factor B (NFB). [7][8][9] An alternative hypothesis is that rAAV transduction is regulated through cellular proliferation or transcription factors rather than through an increase in cellular DNA synthesis.…”
mentioning
confidence: 99%
“…To assess protein production, C12 cells were infected with rAAV1/PA, rAAV1/LF, or rAAV1/eGFP, in the presence of pAdhelper which enhances second-strand synthesis through its E4 ORF6. 30 The lysates from C12 cells infected with rAAV1/PA, rAAV1/LF, or rAAV1/eGFP were collected and assayed by western blotting and demonstrated specific reactivity with antibodies specific for PA, LF, and eGFP, respectively, at their predicted molecular masses (Figure 1d-f).…”
Section: Introductionmentioning
confidence: 99%